Classification of physico-geological models - V. М. Bondarenko; L. Shavier (Известия высших учебных заведений: Геология и разведка, 2023)
Background. A new classification of physico-geological models (PhGM) is presented, which includes system series of models of physico-chemical indicators, geological objects, and geological processes. Such system series models are characterized by physical-mathematical and geotectonic features.Aim. Generalization and systematization of existing models and introduction of new model types, which were not previously considered, to propose a new classification of PhGM.Materials and methods. Scientific publications, including those published by the authors, devoted to the description of various types of models. A systematic review of published data was used as a research method.Results. The proposed classification of PhGM includes system series of models of physico-chemical indicators, geological objects, and geological processes characterized by physico-mathematical and tectonic features.Conclusion. A new classification of PhGM is proposed. This classification generalizes the system series of models of physico-chemical indicators and various geological and physical images. System series of models for diamond-bearing kimberlite pipes and earthquakes are presented.